2021
DOI: 10.29244/jekp.10.2.2021.134-153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Village Funds on the Gap the Human Development Index in Rural-City Areas in Indonesia

Abstract: The development gap is still an important issue. This can be seen in one of the goals in the framework of reference for the development of countries in the world which is formulated in the Sustainable Development Goals (SDGs). One form of inequality that often occurs in the region is the human development gap. The gap in human development in rural and urban areas causes a welfare gap. The gap in human development can be approached from the indicators of the human development index. The Village Fund distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The disparity in human development between villages and cities results in disparities in welfare (Pandiangan et al, 2021). Village finances can increase welfare and equitable village development by increasing public services, developing the economy, closing development gaps between villages, and strengthening communities as development subjects (Rimawan et al, 2020).…”
Section: Human Development and Village Funds Relationshipmentioning
confidence: 99%
See 3 more Smart Citations
“…The disparity in human development between villages and cities results in disparities in welfare (Pandiangan et al, 2021). Village finances can increase welfare and equitable village development by increasing public services, developing the economy, closing development gaps between villages, and strengthening communities as development subjects (Rimawan et al, 2020).…”
Section: Human Development and Village Funds Relationshipmentioning
confidence: 99%
“…To strengthen the capacity of local fund management authorities, regional governments must optimize the village assistance function (Nugraeni and Aji, 2021;Sofilda et al, 2023). Pandiangan et al (2021) concluded that the village funds program negatively influences the gap in Indonesia's human development, using descriptive analysis and analysis of urban village panel data from 2015 to 2019. It is possible to interpret village funding as having a beneficial influence on boosting HDI in Indonesia, as reflected by life expectancy, the gap in average years of schooling, and the disparity per capita in rural and urban areas.…”
Section: Human Development and Village Funds Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Undang-undang Desa No 6 tahun 2014 dijelaskan bahwa Desa yaitu adalah kesatuan masyarakat hukum yang memiliki batas wilayah yang diberi wewenang untuk mengatur dan mengurus urusan pemerintahan, kepentingan masyarakat setempat berdasarkan prakarsa masyarakat, hak asal usul dan/atau hak tradisional yang diakui dan dihormati dalam sistem hukum Pemerintah Negara Kesatuan Republik Indonesia (Pandiangan et al, 2021;Sulistyan & Ermawati, 2020;Isnayanti et al, 2019).…”
Section: Pendahuluanunclassified